GENETIC AND EPIGENETIC FACTORS IN TWIN PREGNANCIES: IMPACT ON MODERN DIAGNOSTICS AND PERINATAL OUTCOME - ERNAZAROVA , MADINA; AXTAMOVA , NILUFAR; SAIDOVA , ZUHRA (GLOBAL SCIENTIFIC RESEARCH AND INTELLECTUAL PURSUITS, 2025)
Twin pregnancies represent a unique biological model for understanding the interplay between genetic and epigenetic mechanisms in human development. While monozygotic twins share nearly identical genomes, phenotypic differences often emerge, suggesting an essential role of epigenetic modifications such as DNA methylation, histone modifications, and non-coding RNAs. Genetic predispositions and epigenetic reprogramming significantly influence fetal growth patterns, placental function, susceptibility to complications such as twin-to-twin transfusion syndrome (TTTS), preterm birth, and intrauterine growth restriction (IUGR). Advances in molecular diagnostics, including next-generation sequencing (NGS), epigenome-wide association studies (EWAS), and non-invasive prenatal testing (NIPT), have enhanced early detection of chromosomal abnormalities, congenital malformations, and perinatal risk stratification in twin gestations. Understanding these genetic and epigenetic factors is essential for optimizing personalized obstetric care, improving perinatal outcomes, and guiding future therapeutic interventions. This article highlights current evidence and emerging perspectives on how molecular biology informs modern diagnostics and perinatal management in twin pregnancies.